Antonio García-Bellido: A brief history of flies, lineages, and a new developmental genetic logic - Jose F. de Celis; Luis A. Baena-López; Antonio Baonza; Cassandra Extavour (Proceedings of the National Academy of Sciences, 2026)
Antonio García-Bellido was a pioneer of developmental biology in Spain who had the rare ability to see beyond the trees and grasp not just the forest, but entire landscapes. Intellectually and personally, he was indefatigable, uncompromising, and wholly committed to science. He led his trainees by example in his unflagging demands on honoring the data above all else. Antonio discovered the existence of “developmental compartments” in the wing of Drosophila and proposed that these territories corresponded to the realm of action of homeotic genes. He was a fierce defender of hypotheses that he thought best explained available data but did not cling blindly to ideas when they no longer served to understand the phenomena at hand. With his distinctive style he founded a successful school of Drosophila developmental geneticists that will sorely miss his unparalleled passion for science.